ECONOMIC AND SPATIAL STRATEGIES OF ARTISTS AS CULTURAL ENTREPRENEURS - Murzyn-Kupisz, Monika; Działek, Jarosław (Quaestiones Geographicae, 2019)
The text aims to explore the economic and spatial strategies followed by artists who run micro-firms. The authors analyse results of a qualitative study of independent artist enterprises in Kraków. It reveals that motivations for artistic entrepreneurship are diverse and foremost linked with the need to overcome challenges artists experience in the labour market and in the market for cultural goods and services. Different strategies translate into particular location choices as well as varied visibility of such firms in urban space.